Análise de métodos para avaliação da qualidade de calçadas - Aguiar, Fabíola de Oliveira (2003)
This dissertation presents the results obtained with the use of different methodologies for the evaluation of the quality of urban pedestrian spaces. The choice of the methodologies was based on a bibliographic review, and those methodologies that best suited the brazilian cities reality were selected. The methodologies were applied in a case study for the evaluation of a pedestrian environment in the city of São Luis, Maranhão. Although each methodology require the collection of a different set of data, the effort to gather all the necessary information was not very great. The analysis showed that the selected methodologies can be easily applied and that, even though they use different quality indicators, the results were virtually identical. It was verified that, according to the applied methodologies, the quality of the pedestrians environment is average, and the results really reflect the conditions of the study area.